Synthesis and characterization of esters derived from ricinoleic acid and evaluation of their low temperature properties - Jumat Salimon; Nadia Salih; Emad Yousif (Universiti Kebangsaan Malaysia, 2012)
A series of ester compounds derived from ricinoleic acid to be used as biolubricants base stock have been synthesized. The resulting products were confirmed by FTIR and NMR analyses. The synthesis was carried out in three stages: epoxidation of ricinoleic acid; synthesis of 10,12-dihydroxy-9-acyloxystearic acid from epoxidized ricinoleic acid with various fatty acids and esterification of the acyloxystearic acid products with octanol to yield octyl-10,12-dihydroxy-9-acyloxystearate. The viscosities, flash points and pour points (PP) behavior of the products were measured. The resulting esters had an increased in molar weight and viscosity and decreased in pour points as compared to ricinoleic acid